Integrated phylogeny of the human brain and pathobiology of Alzheimer's disease: A unifying hypothesis - Ovsepian, Saak V; O'Leary, Valerie B; Hoschl, Cyril; Zaborszky, Laszlo (Neuroscience letters, 2021)
The disproportionate evolutionary expansion of the human cerebral cortex with reinforcement of cholinergic innervations warranted a major rise in the functional and metabolic load of the conserved basal forebrain (BF) cholinergic system. Given that acetylcholine (ACh) regulates properties of the microtubule-associated protein (MAP) tau and promotes non-amyloidogenic processing of amyloid precursor protein (APP), growing neocortex predicts higher demands for ACh, while the emerging role of BF cholinergic projections in Aβ clearance infers greater exposure of source neurons and their innervation fields to amyloid pathology. The higher exposure of evolutionary most recent cortical areas to the amyloid pathology of Alzheimer's disease (AD) with synaptic impairments and atrophy, therefore, might involve attenuated homeostatic effects of BF cholinergic projections, in addition to fall-outs of inherent processes of expanding association areas. This unifying model, thus, views amyloid pathology and loss of cholinergic cells as a quid pro quo of the allometric evolution of the human brain, which in combination with increase in life expectancy overwhelm the fine homeostatic balance and trigger the disease process.
Keywords: Amyloid deposition; proteiny nervové tkáně; Humans; Default Mode Network; Phylogeny; neurony cholinergní; Cholinergic neurons; Nerve Tissue Proteins; Default mode networks; Brain evolution; lidé; Alzheimer Disease; Alzheimer’s disease; zvířata; Alzheimerova nemoc; mozková kůra; Receptors, Nerve Growth Factor; Cerebral Cortex; Cholinergic Neurons; fylogeneze; receptory faktorů růstu nervů; Animals; default mode network; Cortical expansion; p75 NTR